Anwar Ibrahim’s the Asian renaissance revisited - Bakar, Osman; Moon, Ayana Jihye (IIUM Press, 2024)
Nearly three decades ago (1996), the first edition of this book was published by Times Books International. Its author, Anwar Ibrahim, was then one of the most powerful men in Asia. He was the Deputy Prime Minister of Malaysia (1993-1998) and its Minister of Finance (1991-1998), a post which he currently holds for the second time (since 3 December 2022). He is Malaysia’s tenth and present Prime Minister (since 24 November 2022). The book received critical acclaim. It was reprinted in 1997. A new edition was published in 2008 by Marshall Cavendish.